(3efjI GdQVG HQSGFd GdbGVis - (3CHhGdaVd CMeO Hf eMeO Hf CMeO Hf EHQGgje GdejOGfi GdfjSCHhQis; (3efUhQ Hf eMeO Hf eMeO GddROj GdgQhj GdTGaYj, CHh CMeO,J (B440 (3g` s ((3CHh LYaQ eMeO Hf CHj GdaVd GdUGfYi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPg oZQH CdaGX EfJbjJgG eeG YfOi ef cdGe GdbGVi CHj CMeO efUhQ Hf eMeO GdCROi GdgQhi s
(3BNQgG (B:s
(3eeG GSJbd GdHOQ hGSJgd GdbWQ s
(3GfXQ ai GdLRA GdChd GdQbe (B841 (3COHs
(3eNJGQGJ eG hLOg YfOg ef cdGe GdbGVi GdgQhi CHj CMeO efUhQ Hf eMeO GdeJhai (B440 (3hQJHgG ai YTQI CHhGHs
(3fSNI fajSIs
(3HChdgG bQGAI GdfGSN Ydi SYjO Hf CMeO GdejOGfi GdeJhai (B539(3g` hgh GHf GdefJNH s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs